Pelatihan Pembuatan Ice Cream Wortel untuk Komunitas PKK di Desa Wonolelo Magelang - Yasin Muhammad Akbar; Sariyanti Sariyanti; Mega Renny Kumalasari; Ikmal Choirul Huda; Siti Nurjanah; Dwi Indarwati; Kezia Reza Febyani; Ignatia Esti Sumarah (Lembaga Pengembangan Kinerja Dosen, 2024)
Carrots are one of the abundant agricultural products in Wonolelo Village, Magelang. This type of root vegetable contains various nutrients such as Vitamin A, β-carotene, and fiber, which are beneficial for eye health and boosting the immune system against infections. The consumption of fresh carrots is less favored by the community, especially children, so carrot-based processed products in the form of healthy beverages like carrot ice cream can be an attractive and healthy alternative for consumption. The purpose of this activity is to explore the processing of carrots to maximize harvests and optimize the selling value and functionality of carrots as a healthy and appealing product for children. This training uses practical methods, allowing participants to practice and directly process carrots into ice cream. The conclusion of this activity is that it provides insight into carrot processing innovations for the PKK mothers in Wonolelo Village, specifically on how to turn carrots into ice cream, thereby increasing the selling value of carrots, which impacts the welfare of the community, especially carrot farmers.